Rock Stress Around Noncircular Tunnel: A New Simple Mathematical Method (Advances in Applied Mathematics and Mechanics, 2021)
A new simple mathematical method has been proposed to predict rock stressaround a noncircular tunnel and the method is calibrated and validated with a numericalmodel. It can be found that the tunnel shapes and polar angles affect the applicablezone of the theoretical model significantly and the applicable zone of a rectangulartunnel was obtained using this method. The method can be used to predict the valuesof the concentrated stress, and to analyze the change rate of rock stress and back tocalculate the mechanical boundary condition in the applicable zone. The results of thestress change rate indicate that the horizontal stress is negatively related to the verticalboundary load and positively related to the horizontal boundary load. The verticalstress is negatively related to the horizontal boundary load and positively related tothe vertical boundary load. These findings can be used to explain the evolution of thevertical increment in stress obtained with field-based borehole stress monitoring.